POLA PEMAHAMAN KONSEPTUAL SISWA BOARDING SCHOOL DAN NON-BOARDING SCHOOL PADA MATERI KESETIMBANGAN KIMIA - Oktorin, Larissa; Aini, Faizah Qurrata (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study analyzes the conceptual understanding patterns of boarding school and non-boarding school students on chemical equilibrium material. The research was conducted in two madrasas in Padang City, namely one school with a boarding system and one school with a non-boarding system in the 2025/2026 academic year using a qualitative method. The research sample consisted of 100 students in grade XII Phase F, divided into two groups: 50 boarding school students and 50 non-boarding school students. The research instrument was an essay test consisting of four questions designed to measure conceptual understanding. This study shows that there are differences in conceptual understanding patterns between boarding school and non-boarding school students on chemical equilibrium material. Boarding school students tend to have more structured and thorough understanding, although some choose not to answer if they are unsure, while non-boarding school students are more exploratory but their conceptual understanding is less profound. These differences are influenced by the learning environment and academic habits. Both groups still show misconceptions in symbolic and mathematical aspects, emphasizing the need for learning that emphasizes conceptual understanding and multi-level representation in the topic of chemical equilibrium. ABSTRAKPenelitian ini menganalisis pola pemahaman konseptual siswa boarding school dan non boarding school pada materi kesetimbangan kimia. Kegiatan penelitian dilakukan di dua madrasah di Kota Padang, yaitu satu sekolah dengan sistem boarding dan satu sekolah dengan sistem non-boarding tahun ajaran 2025/2026 dengan menggunakan metode kualitatif. Sampel penelitian berjumlah 100 siswa kelas XII Fase F yang dibagi menjadi 2 kelompok: 50 siswa boarding school, dan 50 siswa non-boarding school. Instrumen penelitian berupa tes esai berjumlah empat soal yang dirancang untuk mengukur pemahaman konseptual. Penelitian ini menunjukkan adanya perbedaan pola pemahaman konseptual antara siswa boarding school dan non-boarding school pada materi kesetimbangan kimia. Siswa boarding school cenderung memiliki pemahaman lebih terstruktur dan teliti, meskipun beberapa memilih tidak menjawab jika kurang yakin, sedangkan siswa non-boarding school lebih eksploratif tetapi pemahaman konseptualnya kurang mendalam. Perbedaan ini dipengaruhi oleh lingkungan belajar dan sistem pembiasaan akademik. Kedua kelompok masih menunjukkan miskonsepsi pada aspek simbolik dan matematis, menegaskan perlunya pembelajaran yang menekankan pemahaman konseptual dan representasi multi-level dalam topik kesetimbangan kimia.